Energetic and exergetic Improvement of geothermal single flash cycle - Navid Nazari; Soheil Porkhial (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
This paper presents a detailed analysis of a new method for improving energetic and exergetic efficiencies of single flash cycle. The thermodynamic process of the new method consists of extracting a fraction of hot wellhead geothermal brine for the purpose of superheating saturated steam entering the turbine. Computer programming scripts were developed and optimized based on mathematical proposed models for the different components of the systems. The operating parameters such as separator temperature, geofluid wellhead enthalpy and geothermal source temperature are varied to investigate their effects on both net power output and turbine exhaust quality of the systems. Also, full exergy assessment was performed for the new design. The results of separator temperature optimization revealed that specific net power output of the new design can be boosted up to 8% and turbine exhaust quality can be diminished up to 50% as compared to common single flash cycle. In addition, for wells with higher discharge enthalpy, superheating process improve specific net power output even up to 10%. Finally, it was observed that the overall system exergy efficiency was approximately raised 3%. Article History: Received January 5th 2016; Received in revised form June 25th 2016; Accepted July 3rd 2016; Available onlineHow to Cite This Article: Nazari, N. and Porkhial, S. (2016). Energetic and Exergetic Improvement of Geothermal Single Flash Cycle. Int. Journal of Renewable Energy Development, 5(2),129-138.http://dx.doi.org/10.14710/ijred.5.2.129-138